Role of low dose mitomycin C in pterygium surgery - Thakur, SKD; Kaini, KR; Panda, A (Nepalese Journal of Ophthalmology, 2012)
DOI: http://dx.doi.org/10.3126/nepjoph.v4i1.5881 NEPJOPH 2012; 4(1): 203-205